T lymphocyte-derived demyelinating activity in multiple sclerosis patients in relapse. Issue 5 (May 1987) - Selmaj, K; Alam, R; Perkin, G D; Rose, F C
Abstract : Supernatants of cultured T lymphocytes of multiple sclerosis patients were tested for a demyelinating activity in rat cerebellum explant cultures. Supernatants of unstimulated T lymphocytes in seven out of 10 multiple sclerosis patients in relapse produced demyelination when checked by phase contrast microscopy. Supernatants of unstimulated T lymphocytes from healthy subjects did not produce demyelination, but when T cells were stimulated by phytohaemagglutinin (PHA), 50% of tested supernatants produced demyelination, which was, however, never as advanced as in multiple sclerosis supernatant treated cerebellum cultures. The demyelinating activity proved to be heat labile. Gel filtration study revealed two fractions of the demyelinating activity 12.5-29.0 kD and 43.0-66.0 kD. The results suggest that lymphokines can be directly involved in the pathogenesis of demyelination in multiple sclerosis.